Correlation of low body mass index and albumin level with the presence of liver dysfunction in newly diagnosed tuberculosis patients - Sriyanty Sadsyam; Yulia Yusrini Djabir; Arif Santoso (Universitas Mataram, 2021)
Tuberculosis (TB) patients often experience reduced appetite or nutritional malabsorption leading to malnutrition, which manifests in excessive loss of muscle mass and low body mass index (BMI). Patients with protein malnutrition is associated with increased risk of drug-induced liver injury and may require a close monitoring during the course of antituberculosis (AT) treatment. The purpose of this study was to determine the correlation of low body mass index and albumin level with liver dysfunction in patients newly diagnosed with TB prior to receiving AT drugs. This study is a nonexperimental observational study with consecutive sampling technique by following a descriptive analytic design (cohort study). The subjects were patients in the National Lung Health Center Makassar who are newly diagnosed with TB and have not received any AT drug. The BMI data and blood samples were collected and analyzed to obtain Alanine aminotransferase (ALT), Aspartat aminotransferase (AST), and Albumin levels. It was found that out of 22 total patients, 3 (14%) of the TB patients experienced liver dysfunction characterized by high level of ALT and AST levels. Both patients had normal levels of albumin despite one of them had a low BMI. The statistical showed no correlation between the low BMI or albumin level with the presence of liver dysfunction. It is concluded that the presence of liver dysfunction is not correlated with low BMI or albumin level in newly diagnosed TB patients, and hence, are not considered as independent risk factors of liver dysfunction in this population.